Insights into halloysite or kaolin role of BiVO4 hybrid pigments for applications in polymer matrix and surface coating. (1st October 2019) - Wang, Xiaowen; Mu, Bin; Zhang, Zhe; Wang, Aiqin
Abstract: Two highly thermal-stable clay mineral-based bismuth yellow hybrid pigments were facilely fabricated combining with precipitation and annealing processes using halloysite and kaolin, respectively. The color properties, crystalline phase, morphology, and thermal stability of hybrid pigments were studied. Incorporation of clay minerals not only greatly decreased the production cost of bismuth yellow, but also improved its color properties and thermal stability. After clay mineral-based bismuth yellow hybrid pigments were introduced into polypropylene, the obtained composites exhibited the good mechanical properties compared with polypropylene and polypropylene reinforced with bismuth yellow, which was mainly attributed to the synergistic effect between clay minerals and bismuth yellow. It suggested that the as-prepared bismuth yellow hybrid pigments could be simultaneously served as a promising colorant and toughening and strengthening materials to be applied in plastic. In addition, the bismuth yellow hybrid pigments also presented the outstanding flame retardancy after being coated on polyurethane foam. Graphical abstract: Image 1 Highlights: Highly thermal-stable clay mineral/bismuth yellow hybrid pigments were prepared. PP reinforced with hybrid pigments presented good mechanical properties. Hybrid pigments could be simultaneously served as colorant and reinforced materials. PU foam coated hybrid pigments exhibited outstanding flame retardancy.